Vaccination inducing durable and robust antigen-specific Th1/Th17 immune responses contributes to prophylactic protection against Mycobacterium avium infection but is ineffective as an adjunct to antibiotic treatment in chronic disease. Issue 1 (31st December 2022) - Lee, Ju Mi; Park, Jiyun; Reed, Steven G; Coler, Rhea N; Hong, Jung Joo; Kim, Lee-Han; Lee, Wonsik; Kwon, Kee Woong; Shin, Sung Jae
ABSTRACT: Mycobacterium avium complex (MAC) causing pulmonary disease in humanshas emerged worldwide. Thus, effective strategies simultaneously aiming to prevent MAC infection and accelerate therapeutic efficacy are required. To this end, subunit vaccine-induced protection against a well-defined virulent Mycobacterium avium (Mav) isolate was assessed as a preventative and therapeutic modality in murine models. Mav-derived culture filtrate antigen (CFA) was used as a vaccine antigen with glucopyranosyl lipid A stable emulsion (GLA-SE) or GLA-SE plus cyclic-di-GMP (GLA-SE/CDG), and we compared the immunogenicities, protective efficacies and immune correlates. Interestingly, CFA+GLA-SE/CDG immunization induced greater CFA-specific Th1/Th17 responses in both the lung and spleen than among the tested groups. Consequently, protective efficacy was optimally achieved with CFA+GLA-SE/CDG by significantly reducing bacterial loads along with long-lasting maintenance of antigen-specific Th1/Th17 cytokine-producing multifunctional T cell responses and relevant cytokine productions. Thus, we employed this subunit vaccine as an adjunct to antibiotic treatment. However, this vaccine was ineffective in further reducing bacterial loads. Collectively, our study demonstrates that strong Mav CFA-specific Th1/Th17 responses are critical for preventative protection against Mav infection but may be ineffective or even detrimental in an established and progressive chronic disease, indicating that different approaches to combating Mav infection are necessary according to vaccination purposes.